Government Digital Marketing Communications for Tourism Development in Bejijong Village - Mardiatna, Pradana Tera; Joko Prasetyo, Iwan; Panuju, Redi; Syam Maella, Nurannafi Farni (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study aims to analyze the tourism potential and marketing strategies in Bejijong Village, a village with a rich history and culture from the Majapahit Kingdom era located in Mojokerto Regency, East Java Province. This study explores how village managers conduct managerial and marketing activities to attract tourists and promote local products. The research method involves a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in the Marketing Mix’s 7P approach implemented by the village. The results of the study indicate that Bejijong Village has several significant advantages, including historical heritage such as Brahu Temple, Petilasan Siti Inggil, and Maha Vihara Majapahit, as well as local products such as smoked salted eggs, lemon juice, pukis lumer (melting) bertoping, tahu lontong (compress rice), and Cempaka batik handicrafts and wayang kulit. However, the challenges faced include less than optimal website management, lack of effective digital marketing strategies, and entrance fees that may be insufficient to support maintenance. This study introduces novelty in marketing strategy analysis by integrating the SWOT and Marketing Mix’s 7P approaches to provide in-depth insights into how management and marketing can be improved. These findings are expected to be a reference for other villages in designing more effective marketing strategies and suggesting improvement steps that can increase the attractiveness and sustainability of culture-based tourist destinations. Keywords: Bejijong Village, Tourism Marketing, SWOT Analysis, Marketing Mix 7P.